Degradable hot melt adhesive and preparation method thereof

By adding special toughening modifiers and reinforcement fillers to the polylactic acid hot melt adhesive, the problems of brittleness and poor toughness of the polylactic acid hot melt adhesive are solved, and its toughness and bonding properties are significantly improved. It is suitable for application scenarios that require high impact strength and ultraviolet resistance.

CN119859499APending Publication Date: 2025-04-22GUANGZHOU WEASY ADHESIVE PROD CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510242608.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Polylactic acid hot melt adhesive is easily brittle and has poor toughness after curing, which limits its use in applications requiring high impact strength or high toughness.

Method used

By adding toughening modifiers, reinforcement fillers and citrate esters, the toughness and bonding properties of polylactic acid hot melt adhesive are improved. The toughening modifier is synthesized by specific steps, and the reinforcement filler is made by synergistically acting on modified sodium alginate, maleic anhydride and modified calcium carbonate.

Benefits of technology

It significantly improves the toughness and bonding properties of polylactic acid hot melt adhesive, enhances its performance in impact strength and resistance to ultraviolet rays, reduces defects such as cracking and blistering, and enhances the overall texture and aesthetics of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of hot melt adhesives, and discloses a degradable hot melt adhesive and a preparation method thereof. The hot melt adhesive is prepared from the following raw materials in parts by weight: 60 to 80 parts of polylactic acid, 7 to 12 parts of toughening modifier, 6 to 10 parts of reinforcing filler, 1.5 to 2.5 parts of plasticizer, 0.5 to 1.5 parts of antioxidant and 3 to 5 parts of polyethylene wax, according to the hot melt adhesive, polylactic acid with good degradability is used as a main raw material, and functional aids such as a modified flexibilizer and a reinforcing filler are added, so that the degradability, toughness, bonding strength, ultraviolet resistance and the like of the hot melt adhesive are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hot melt adhesives, and in particular to a degradable hot melt adhesive and a preparation method thereof. Background Art

[0002] With the increasing global environmental awareness and the pursuit of sustainable development, the environmental problems of traditional non-degradable materials have become increasingly prominent. Hot melt adhesives are widely used in packaging, textiles, automobiles, electronics and other fields. They are mainly EVA and polyurethane. Their non-degradability has led to a large amount of waste accumulation, which has caused a serious burden on the environment.

[0003] Polylactic acid (PLA) is a polymer material with good biodegradability and biocompatibility. It is mainly made by polymerizing lactic acid and has the advantages of wide sources, renewable and degradable. The hot melt adhesive prepared by using polylactic acid as the main raw material and adding additives has the bonding performance requirements of traditional hot melt adhesives, and can also degrade naturally after use to reduce the impact on the environment. However, polylactic acid hot melt adhesive still has obvious disadvantages. For example, polylactic acid hot melt adhesive is brittle and has poor toughness after curing. It is easy to crack or break when subjected to external force, which to a certain extent limits its use in application scenarios that require high impact strength or high toughness. Therefore, it is necessary to improve the toughness of polylactic acid hot melt adhesive by adding toughening agents, elastomers or fillers so that it has a wider application environment. Summary of the invention

[0004] In order to solve the problem that polylactic acid hot melt adhesive is brittle and has poor toughness after curing, the present invention provides a degradable hot melt adhesive and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A degradable hot melt adhesive comprises the following raw materials in parts by weight: 60-80 parts of polylactic acid, 7-12 parts of a toughening modifier, 6-10 parts of a reinforcing filler, 1.5-2.5 parts of a plasticizer, 0.5-1.5 parts of an antioxidant, and 3-5 parts of polyethylene wax; The plasticizer is a citrate, and the antioxidant is one of antioxidant 1010 or antioxidant 168; The toughening modifier is prepared by the following steps: Step A1, the pre-treated 6-amino-n-hexanoic acid and tetrahydrofuran are mixed evenly, 1-hydroxybenzotriazole is added, and the mixture is stirred in an ice-water bath for 30 minutes, and then concentrated sulfuric acid is added, and the mixture is vigorously stirred at 60-80° C. for 12-16 hours. After cooling to 30° C., 50wt% acetic acid solution is added and refluxed for 10 minutes, and the mixture is concentrated under reduced pressure and purified to obtain an amino-terminated benzotriazole derivative; Step A2, mixing an amino-terminated benzotriazole derivative, sodium hydroxide and acetonitrile, recorded as a mixed solution A; mixing 2-aminoterephthalic acid, sodium hydroxide and acetonitrile, recorded as a mixed solution B; mixing cyanuric chloride and acetonitrile in an ice-water bath, slowly adding half of the mixed solution A, reacting for 2-3 hours, heating to 45-55° C., adding the remaining half of the mixed solution A, reacting for 2-3 hours, then heating to 90° C., adding the mixed solution B, reacting for 4-6 hours, filtering, washing and drying to obtain a triazine-benzotriazole derivative; Step A3, adding triazine-benzotriazole derivatives, terephthalic acid, adipic acid and 1,4-butanediol into an esterification kettle, heating and stirring to 150° C., then adding tetrabutyl titanate, stirring, heating to 180-200° C., reacting for 2-4 hours, then evacuating to 100 KPa, reacting at 220° C. for 4-5 hours, cooling, and pelletizing to obtain a toughening modifier; Furthermore, in step A1, the molar ratio of 6-amino-n-hexanoic acid to 1-hydroxybenzotriazole in the pretreatment is 1:1.3-1.5, the amount of concentrated sulfuric acid is 2-4wt% of the mass of 1-hydroxybenzotriazole, and the volume of the acetic acid solution is 50mL; Furthermore, the pre-treated 6-amino-n-hexanoic acid in step A1 is 6-amino-n-hexanoic acid treated with a trityl protecting group; Furthermore, in step A2, the dosage ratio of cyanuric chloride, acetonitrile, mixed solution A and mixed solution B is 0.01-0.03 mol: 100 mL: 100 mL: 50 mL; Further, in step A2, the amount ratio of the terminal aminobenzotriazole derivative, sodium hydroxide and acetonitrile in the mixed solution A is 0.02-0.06 mol: 0.1-0.25 g: 100 mL, and the amount ratio of 2-aminoterephthalic acid, sodium hydroxide and acetonitrile in the mixed solution B is 0.01-0.03 mol: 0.04-0.12 g: 50 mL; Furthermore, in step A3, the molar ratio of the total molar amount of the triazine-benzotriazole derivative, terephthalic acid and adipic acid to 1,4-butanediol is 1:1.2-2; Further, in step A3, the molar ratio of the triazine-benzotriazole derivative, terephthalic acid and adipic acid is 0.1-0.3:0.1-0.6:0.1-0.8; Furthermore, in step A3, the amount of tetrabutyl titanate added is 0.2 to 0.5‰ of the total mass of the triazine-benzotriazole derivative, terephthalic acid and adipic acid.

[0006] The reinforcing filler is prepared by the following steps: Step B1, dispersing sodium alginate in MES buffer at pH 6, adding EDC (1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride) and NHS (N-hydroxysuccinimide) and stirring for 20 minutes, then adding 2-aminoethyl methacrylate hydrochloride and stirring for 24 hours, then adding ethanol for precipitation, filtering, washing and drying to obtain modified sodium alginate; Step B2, 3-trimethoxysilane propyl acrylate, ethanol and deionized water are mixed, calcium carbonate is added, and the mixture is stirred at 35° C. for 24 hours, filtered, washed and the precipitate is collected to obtain modified calcium carbonate; maleic anhydride, modified sodium alginate, modified calcium carbonate and benzoyl peroxide are then mixed in toluene, the mixture is heated to 50° C. and stirred for 20 minutes, and then the mixture is heated to 80-90° C. and reacted for 2-4 hours, and then methanol is added and allowed to stand for 2 hours, filtered, washed and dried to obtain a reinforcing filler; Further, in step B1, the usage ratio of sodium alginate, MES buffer, EDC, NHS and 2-aminoethyl methacrylate hydrochloride is 1-3 g: 100 mL: 0.02-0.04 mol: 0.01-0.02 mol: 0.01-0.03 mol; Further, in step B2, the dosage ratio of maleic anhydride, modified sodium alginate, modified calcium carbonate, benzoyl peroxide, toluene and methanol is 2-4 g: 1-3 g: 3-5 g: 0.03-0.06 g: 100 mL: 200 mL; Furthermore, in step B2, the dosage ratio of 3-trimethoxysilane propyl acrylate, ethanol, deionized water and calcium carbonate in the modified calcium carbonate is 0.5-2 mL: 80 mL: 20 mL: 3-6 g.

[0007] A method for preparing a degradable hot melt adhesive comprises the following steps: Weigh the raw materials by weight, mix polylactic acid, toughening modifier, reinforcing filler, antioxidant, plasticizer and polyethylene wax evenly, extrude, cool and granulate in a twin-screw extruder to obtain a degradable hot melt adhesive; Furthermore, the temperature of each section of the twin-screw extruder is controlled at 180-200° C., and the screw speed is 50-90 r / min.

[0008] Beneficial effects of the present invention: In this application, the toughness of the polylactic acid hot melt adhesive is improved by adding a toughening modifier. The main chain of the toughening modifier contains a large number of non-polar methylene structures and ester groups, which makes the material have excellent toughness. After being introduced into the matrix, the toughness of the polylactic acid can be significantly improved. This is because the modified toughening agent in the matrix can absorb energy by using the silver streaks or shear bands generated when external forces impact, thereby improving the impact strength of the matrix, so that the hot melt adhesive can better fit the material in processes such as edge sealing and veneer, reduce defects such as cracking and blistering, and improve the overall texture and aesthetics of the product. In addition, the maleic anhydride group in the reinforcing filler can be used to react with the hydroxyl group in the toughening modifier or the polylactic acid molecular chain, and the reinforcing filler can be used as a bridge to improve the compatibility of the toughening modifier in the matrix.

[0009] The present application utilizes modified sodium alginate, maleic anhydride and modified calcium carbonate to polymerize to obtain a reinforcing filler, which can not only improve the toughness of the matrix, but also improve the bonding performance of the matrix; sodium alginate and calcium carbonate can work synergistically to adjust the viscosity of the matrix and improve the bonding performance, while the emulsification performance of sodium alginate is utilized to make the components in the matrix evenly mixed; in addition, calcium carbonate can also serve as a concentration point when the matrix is ​​subjected to external stress, absorb and disperse energy, and thus improve the toughness of the matrix.

[0010] The side chain of the modified toughening agent of the present application also introduces a benzotriazole group and a triazine structure with ultraviolet absorption effect. The two work synergistically to improve the anti-ultraviolet effect of the matrix, which can effectively reduce the damage of ultraviolet rays to the molecular structure in the matrix and avoid the reduction of bonding strength and performance degradation caused by molecular structure damage. DETAILED DESCRIPTION

[0011] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0012] The pre-treated 6-amino-n-hexanoic acid in the embodiment of the present application is prepared by the following steps: 0.01 mol 6-amino-n-hexanoic acid, 20 mL chloroform and 4 mL acetonitrile are mixed, 0.01 mol trimethylsilyl chloride is added, refluxed for 2 h, cooled to 0°C, 0.02 mol triethylamine, 0.015 mol trityl chloride and 10 mL chloroform are added, and the mixture is stirred for 1 h, and 2 mL methanol is added, concentrated, extracted and dried to obtain the pre-treated 6-amino-n-hexanoic acid.

[0013] Example 1: The toughening modifier is prepared by the following steps: Step A1, 0.01 mol of pre-treated 6-amino n-hexanoic acid and 100 mL of tetrahydrofuran were mixed evenly, 0.013 mol of 1-hydroxybenzotriazole was added, and the mixture was stirred in an ice-water bath for 30 min, and concentrated sulfuric acid was added, and the mixture was vigorously stirred at 60° C. for 12 h. After cooling to 30° C., 50 mL of 50 wt% acetic acid solution was added, and the mixture was refluxed for 10 min, concentrated under reduced pressure, and purified to obtain an amino-terminated benzotriazole derivative, wherein the concentrated sulfuric acid is 2 wt% of the mass of 1-hydroxybenzotriazole; Step A2, 0.02 mol of terminal aminobenzotriazole derivative, 0.1 g of sodium hydroxide and 100 mL of acetonitrile were mixed, recorded as mixed solution A; 0.01 mol of 2-aminoterephthalic acid, 0.04 g of sodium hydroxide and 50 mL of acetonitrile were mixed, recorded as mixed solution B; 0.01 mol of cyanuric chloride and 100 mL of acetonitrile were mixed in an ice-water bath, half of the mixed solution A was slowly added, reacted for 2 h, heated to 45 ° C, the remaining half of the mixed solution A was added, reacted for 2 h, then heated to 90 ° C, mixed solution B was added, reacted for 4 h, filtered, washed and dried to obtain a triazine-benzotriazole derivative; Step A3, add 0.1 mol of triazine-benzotriazole derivative, 0.6 mol of terephthalic acid, 0.3 mol of adipic acid and 1.2 mol of 1,4-butanediol into an esterification kettle, heat and stir to 150°C, then add tetrabutyl titanate, stir, heat to 180°C, react for 2h, then evacuate to 100KPa, and react at 220°C for 4h, cool, and pelletize to obtain a toughening modifier. The amount of tetrabutyl titanate added is 0.2‰ of the total mass of the triazine-benzotriazole derivative, terephthalic acid and adipic acid.

[0014] The reinforcing filler is prepared by the following steps: Step B1, dispersing 1 g of sodium alginate in 100 mL of MES buffer at pH 6, adding 0.02 mol of EDC and 0.01 mol of NHS and stirring for 20 min, then adding 0.01 mol of 2-aminoethyl methacrylate hydrochloride and stirring for 24 h, then adding ethanol for precipitation, filtering, washing and drying to obtain modified sodium alginate; Step B2, 0.5mL 3-trimethoxysilane propyl acrylate, 80mL ethanol and 20mL deionized water were mixed, 3g calcium carbonate was added, and the mixture was stirred at 35°C for 24h, filtered, washed and the precipitate was collected to obtain modified calcium carbonate; then 2g maleic anhydride, 1g modified sodium alginate, 3g modified calcium carbonate and 0.03g benzoyl peroxide were mixed in 100mL toluene, the mixture was heated to 50°C and stirred for 20min, then heated to 80°C and reacted for 2h, then 200mL methanol was added and allowed to stand for 2h, filtered, washed and dried to obtain a reinforcing filler.

[0015] Example 2: The toughening modifier is prepared by the following steps: Step A1, 0.01 mol of pre-treated 6-amino n-hexanoic acid and 100 mL of tetrahydrofuran were mixed evenly, 0.014 mol of 1-hydroxybenzotriazole was added, and the mixture was stirred in an ice-water bath for 30 min, and concentrated sulfuric acid was added, and the mixture was vigorously stirred at 70° C. for 14 h. After cooling to 30° C., 50 mL of 50 wt% acetic acid solution was added and refluxed for 10 min, and the mixture was concentrated under reduced pressure and purified to obtain an amino-terminated benzotriazole derivative, wherein the concentrated sulfuric acid was 3 wt% of the mass of 1-hydroxybenzotriazole; Step A2, 0.04 mol of terminal aminobenzotriazole derivative, 0.18 g of sodium hydroxide and 100 mL of acetonitrile were mixed, recorded as mixed solution A; 0.02 mol of 2-aminoterephthalic acid, 0.08 g of sodium hydroxide and 50 mL of acetonitrile were mixed, recorded as mixed solution B; 0.02 mol of cyanuric chloride and 100 mL of acetonitrile were mixed in an ice-water bath, half of the mixed solution A was slowly added, reacted for 2.5 h, heated to 50 ° C, the remaining half of the mixed solution A was added, reacted for 2.5 h, then heated to 90 ° C, mixed solution B was added, reacted for 5 h, filtered, washed and dried to obtain a triazine-benzotriazole derivative; Step A3, add 0.2 mol of triazine-benzotriazole derivative, 0.4 mol of terephthalic acid, 0.4 mol of adipic acid and 1.5 mol of 1,4-butanediol into an esterification kettle, heat and stir to 150°C, then add tetrabutyl titanate, stir, heat to 190°C, react for 3h, then evacuate to 100KPa, react at 220°C for 4.5h, cool, and pelletize to obtain a toughening modifier. The amount of tetrabutyl titanate added is 0.35‰ of the total mass of the triazine-benzotriazole derivative, terephthalic acid and adipic acid.

[0016] The reinforcing filler is prepared by the following steps: Step B1, dispersing 2 g of sodium alginate in 100 mL of MES buffer at pH 6, adding 0.03 mol of EDC and 0.015 mol of NHS and stirring for 20 min, then adding 0.02 mol of 2-aminoethyl methacrylate hydrochloride and stirring for 24 h, then adding ethanol for precipitation, filtering, washing and drying to obtain modified sodium alginate; Step B2, 1mL 3-trimethoxysilane propyl acrylate, 80mL ethanol and 20mL deionized water were mixed, 4.5g calcium carbonate was added, and the mixture was stirred at 35°C for 24h, filtered, washed and the precipitate was collected to obtain modified calcium carbonate; 3g maleic anhydride, 2g modified sodium alginate, 4g modified calcium carbonate and 0.045g benzoyl peroxide were mixed in 100mL toluene, the mixture was heated to 50°C and stirred for 20min, then heated to 85°C and reacted for 3h, 200mL methanol was added and allowed to stand for 2h, filtered, washed and dried to obtain a reinforcing filler.

[0017] Example 3: The toughening modifier is prepared by the following steps: Step A1, 0.01 mol of pre-treated 6-amino n-hexanoic acid and 100 mL of tetrahydrofuran were mixed evenly, 0.015 mol of 1-hydroxybenzotriazole was added, and the mixture was stirred in an ice-water bath for 30 min, and concentrated sulfuric acid was added, and the mixture was vigorously stirred at 80° C. for 16 h. After cooling to 30° C., 50 mL of 50 wt% acetic acid solution was added, and the mixture was refluxed for 10 min, concentrated under reduced pressure, and purified to obtain an amino-terminated benzotriazole derivative, wherein the concentrated sulfuric acid was 4 wt% of the mass of 1-hydroxybenzotriazole; Step A2, 0.06 mol of terminal aminobenzotriazole derivative, 0.25 g of sodium hydroxide and 100 mL of acetonitrile were mixed, recorded as mixed solution A; 0.03 mol of 2-aminoterephthalic acid, 0.12 g of sodium hydroxide and 50 mL of acetonitrile were mixed, recorded as mixed solution B; 0.03 mol of cyanuric chloride and 100 mL of acetonitrile were mixed in an ice-water bath, half of the mixed solution A was slowly added, reacted for 3 h, heated to 55 ° C, the remaining half of the mixed solution A was added, reacted for 3 h, then heated to 90 ° C, mixed solution B was added, reacted for 6 h, filtered, washed and dried to obtain a triazine-benzotriazole derivative; Step A3, add 0.3 mol of triazine-benzotriazole derivative, 0.2 mol of terephthalic acid, 0.5 mol of adipic acid and 2 mol of 1,4-butanediol into an esterification kettle, heat and stir to 150°C, then add tetrabutyl titanate, stir, heat to 200°C, react for 4 hours, then evacuate to 100 KPa, and react at 220°C for 4-5 hours, cool, and pelletize to obtain a toughening modifier. The amount of tetrabutyl titanate added is 0.5‰ of the total mass of the triazine-benzotriazole derivative, terephthalic acid and adipic acid.

[0018] The reinforcing filler is prepared by the following steps: Step B1, dispersing 3 g of sodium alginate in 100 mL of MES buffer at pH 6, adding 0.04 mol of EDC and 0.02 mol of NHS and stirring for 20 min, then adding 0.03 mol of 2-aminoethyl methacrylate hydrochloride and stirring for 24 h, then adding ethanol for precipitation, filtering, washing and drying to obtain modified sodium alginate; Step B2, 2mL of 3-trimethoxysilane propyl acrylate, 80mL of ethanol and 20mL of deionized water were mixed, 6g of calcium carbonate was added, and the mixture was stirred at 35°C for 24h, filtered, washed and the precipitate was collected to obtain modified calcium carbonate; 4g of maleic anhydride, 3g of modified sodium alginate, 5g of modified calcium carbonate and 0.06g of benzoyl peroxide were mixed in 100mL of toluene, the mixture was heated to 50°C and stirred for 20min, then heated to 90°C and reacted for 4h, 200mL of methanol was added and allowed to stand for 2h, filtered, washed and dried to obtain a reinforcing filler.

[0019] Embodiment 4: A method for preparing a degradable hot melt adhesive comprises the following steps: 60 parts of polylactic acid, 7 parts of the toughening modifier prepared in Example 1, 6 parts of the reinforcing filler prepared in Example 1, 1.5 parts of citrate, 0.5 parts of antioxidant 168, and 3 parts of polyethylene wax; The raw materials were weighed by weight, and polylactic acid, the toughening modifier prepared in Example 1, the reinforcing filler prepared in Example 1, the antioxidant 168, the citrate and the polyethylene wax were evenly mixed, and then extruded, cooled and granulated in a twin-screw extruder to obtain a degradable hot melt adhesive. The temperature of each section of the twin-screw extruder was controlled at 180°C and the screw speed was 50r / min.

[0020] Embodiment 5: A method for preparing a degradable hot melt adhesive comprises the following steps: 70 parts of polylactic acid, 10 parts of the toughening modifier prepared in Example 2, 8 parts of the reinforcing filler prepared in Example 2, 2 parts of citrate, 1 part of antioxidant 1010, and 4 parts of polyethylene wax; The raw materials were weighed by weight, and polylactic acid, the toughening modifier prepared in Example 2, the reinforcing filler prepared in Example 2, the antioxidant 1010, the citrate and the polyethylene wax were evenly mixed, and then extruded, cooled and granulated in a twin-screw extruder to obtain a degradable hot melt adhesive. The temperature of each section of the twin-screw extruder was controlled at 190°C and the screw speed was 70r / min.

[0021] Embodiment 6: A method for preparing a degradable hot melt adhesive comprises the following steps: 80 parts of polylactic acid, 12 parts of the toughening modifier prepared in Example 3, 10 parts of the reinforcing filler prepared in Example 3, 2.5 parts of citrate, 1.5 parts of antioxidant 1010, and 5 parts of polyethylene wax; The raw materials were weighed by weight, and polylactic acid, the toughening modifier prepared in Example 3, the reinforcing filler prepared in Example 3, the antioxidant 1010, the citrate and the polyethylene wax were evenly mixed, and then extruded, cooled and granulated in a twin-screw extruder to obtain a degradable hot melt adhesive. The temperature of each section of the twin-screw extruder was controlled at 200°C and the screw speed was 90r / min.

[0022] Comparative Example 1: This comparative example is a hot melt adhesive. The difference from Example 6 is that acrylonitrile-butadiene-styrene terpolymer is used instead of the toughening modifier prepared in Example 3, and 5 parts of commercially available ultraviolet absorber UV328 are added, and the rest are the same.

[0023] Comparative Example 2: This comparative example is a hot melt adhesive. The difference from Example 6 is that calcium carbonate is used instead of the reinforcing filler prepared in Example 3, and the rest is the same.

[0024] Comparative Example 3: This comparative example is a hot melt adhesive. The difference from Example 6 is that acrylonitrile-butadiene-styrene terpolymer is used instead of the toughening modifier prepared in Example 3, and calcium carbonate is used instead of the reinforcing filler prepared in Example 3. The rest are the same.

[0025] The hot melt adhesives prepared in Examples 4-6 and Comparative Examples 1-3 were subjected to performance tests: Degradability test: The hot melt adhesive is evenly coated on the release paper, and placed in an environment of 25°C and 60% humidity to cure naturally. The film is removed to make several pieces of the same size and thickness, and buried in the soil. A piece is taken out at regular intervals, and the remaining mass percentage is recorded after cleaning and drying. Adhesive strength test: Apply hot melt adhesive evenly between two PVC plastic plates, place the bonded samples in a 50°C, 60% humidity environment for natural curing, and test the peel strength of the cured samples; Toughness test: The hot melt adhesive is evenly coated between the PVC plastic plate and the impregnated paper. After hot pressing and curing, a 350g round iron ball is used to freely fall from a certain height to hit the sample. The impact strength is evaluated by observing the fracture of the sample and measuring the height of the falling hammer. Anti-ultraviolet performance test: The hot melt adhesive is evenly coated into a thin film and evenly rolled into a sample with a thickness of 0.5mm. The sample is exposed to UV light, and the light and condensation temperatures are 60℃ and 40℃ respectively, for 4 hours. The light and condensation are carried out alternately, and the total time is 1000 hours. The yellowing index (ΔYI) after anti-ultraviolet aging is tested according to GB2409-80 "Plastic Yellowness Index Test Method"; The test results are shown in Table 1:

[0026] As can be seen from Table 1, after the degradation test, the residual mass of the hot melt adhesive prepared by the present invention is less than or equal to 3% at 18 months, indicating that the hot melt adhesive has good degradation performance; after the peel strength test, the peel strength of the hot melt adhesive is (9.1-9.6) N / 25mm, indicating that it has good bonding performance; after the toughness test, the crack drop height of the hot melt adhesive is (1.6-1.8) m, indicating that it has good toughness; after the ultraviolet aging test, the yellowing index (ΔYI) is 0.18-0.21, indicating that it has good anti-ultraviolet aging performance.

[0027] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A degradable hot melt adhesive, characterized in that: The invention comprises the following raw materials in parts by weight: 60-80 parts of polylactic acid, 7-12 parts of toughening modifier, 6-10 parts of reinforcing filler, 1.5-2.5 parts of plasticizer, 0.5-1.5 parts of antioxidant and 3-5 parts of polyethylene wax; The plasticizer is a citrate, and the antioxidant is one of antioxidant 1010 or antioxidant 168; The toughening modifier is synthesized from triazine-benzotriazole derivatives, terephthalic acid, adipic acid and 1,4-butanediol as raw materials; the triazine-benzotriazole derivative is prepared by substitution reaction of cyanuric chloride, amino-terminated benzotriazole derivative and 2-aminoterephthalic acid; the amino-terminated benzotriazole derivative is prepared by esterification reaction of 1-hydroxybenzotriazole and pre-treated 6-amino-n-hexanoic acid; the pre-treated 6-amino-n-hexanoic acid is 6-amino-n-hexanoic acid treated with a trityl protecting group; The reinforcing filler is prepared by polymerization reaction of modified sodium alginate, modified calcium carbonate and maleic anhydride, the modified sodium alginate is prepared by mixing sodium alginate and 2-aminoethyl methacrylate hydrochloride, and the modified calcium carbonate is obtained by modification of 3-trimethoxysilane propyl acrylate.

2. A degradable hot melt adhesive according to claim 1, characterized in that: The toughening modifier is prepared by the following steps: Step A1, the pre-treated 6-amino-n-hexanoic acid and tetrahydrofuran are mixed evenly, 1-hydroxybenzotriazole is added, and the mixture is stirred in an ice-water bath for 30 minutes, and then concentrated sulfuric acid is added, and the mixture is vigorously stirred at 60-80° C. for 12-16 hours. After cooling to 30° C., 50wt% acetic acid solution is added and refluxed for 10 minutes, and the mixture is concentrated under reduced pressure and purified to obtain an amino-terminated benzotriazole derivative; Step A2, mixing an amino-terminated benzotriazole derivative, sodium hydroxide and acetonitrile, recorded as a mixed solution A; mixing 2-aminoterephthalic acid, sodium hydroxide and acetonitrile, recorded as a mixed solution B; mixing cyanuric chloride and acetonitrile in an ice-water bath, slowly adding half of the mixed solution A, reacting for 2-3 hours, heating to 45-55° C., adding the remaining half of the mixed solution A, reacting for 2-3 hours, then heating to 90° C., adding the mixed solution B, reacting for 4-6 hours, filtering, washing and drying to obtain a triazine-benzotriazole derivative; Step A3, add triazine-benzotriazole derivatives, terephthalic acid, adipic acid and 1,4-butanediol into an esterification kettle, heat and stir to 150°C, then add tetrabutyl titanate, stir, heat to 180-200°C, react for 2-4h, then evacuate to 100KPa, react at 220°C for 4-5h, cool, and pelletize to obtain a toughening modifier.

3. A degradable hot melt adhesive according to claim 2, characterized in that: In step A1, the molar ratio of 6-aminohexanoic acid and 1-hydroxybenzotriazole in the pretreatment is 1:1.3-1.5, the concentrated sulfuric acid is 2-4wt% of the mass of 1-hydroxybenzotriazole, and the volume of the acetic acid solution is 50mL.

4. The degradable hot melt adhesive according to claim 2, characterized in that: In step A2, the dosage ratio of cyanuric chloride, acetonitrile, mixed solution A and mixed solution B is 0.01-0.03 mol: 100 mL: 100 mL: 50 mL, the dosage ratio of terminal aminobenzotriazole derivative, sodium hydroxide and acetonitrile in mixed solution A is 0.02-0.06 mol: 0.1-0.25 g: 100 mL, and the dosage ratio of 2-aminoterephthalic acid, sodium hydroxide and acetonitrile in mixed solution B is 0.01-0.03 mol: 0.04-0.12 g: 50 mL.

5. The degradable hot melt adhesive according to claim 2, characterized in that: In step A3, the molar ratio of the total molar amount of triazine-benzotriazole derivatives, terephthalic acid and adipic acid to 1,4-butanediol is 1:1.2-2, and the molar ratio of triazine-benzotriazole derivatives, terephthalic acid and adipic acid is 0.1-0.3:0.1-0.6:0.1-0.

8.

6. The degradable hot melt adhesive according to claim 2, characterized in that: In step A3, the amount of tetrabutyl titanate added is 0.2 to 0.5‰ of the total mass of the triazine-benzotriazole derivative, terephthalic acid and adipic acid.

7. The degradable hot melt adhesive according to claim 1, characterized in that: The reinforcing filler is prepared by the following steps: Step B1, dispersing sodium alginate in MES buffer with a pH of 6, adding EDC and NHS and stirring for 20 minutes, then adding 2-aminoethyl methacrylate hydrochloride and stirring for reaction for 24 hours, then adding ethanol for precipitation, filtering, washing and drying to obtain modified sodium alginate; Step B2, 3-trimethoxysilane acrylate, ethanol and deionized water are mixed, calcium carbonate is added, and the mixture is stirred at 35°C for 24 hours. The mixture is filtered, washed and the precipitate is collected to obtain modified calcium carbonate. Maleic anhydride, modified sodium alginate, modified calcium carbonate and benzoyl peroxide are then mixed in toluene, the mixture is heated to 50°C and stirred for 20 minutes, the mixture is heated to 80-90°C and reacted for 2-4 hours, methanol is added and the mixture is allowed to stand for 2 hours, the mixture is filtered, washed and dried to obtain a reinforcing filler.

8. The degradable hot melt adhesive according to claim 7, characterized in that: In step B1, the usage ratio of sodium alginate, MES buffer, EDC, NHS and 2-aminoethyl methacrylate hydrochloride is 1-3 g:100 mL:0.02-0.04 mol:0.01-0.02 mol:0.01-0.03 mol.

9. The degradable hot melt adhesive according to claim 7, characterized in that: In step B2, the dosage ratio of maleic anhydride, modified sodium alginate, modified calcium carbonate, benzoyl peroxide, toluene and methanol is 2-4g:1-3g:3-5g:0.03-0.06g:100mL:200mL, and the dosage ratio of 3-trimethoxysilane propyl acrylate, ethanol, deionized water and calcium carbonate in the modified calcium carbonate is 0.5-2mL:80mL:20mL:3-6g.

10. A method for preparing the degradable hot melt adhesive according to any one of claims 1 to 9, characterized in that: The following steps are involved: The raw materials are weighed by weight, polylactic acid, toughening modifier, reinforcing filler, antioxidant, plasticizer and polyethylene wax are evenly mixed, and then extruded, cooled and granulated in a twin-screw extruder to obtain a degradable hot melt adhesive. The temperature of each section of the twin-screw extruder is controlled at 180-200°C, and the screw speed is 50-90r / min.